Hexamethylenetetramine: an effective and universal nitrogen-doping reagent to enhance the photoluminescence of carbon nanodots. (6th February 2018) - Wang, Yi; Zhang, Pu; Ye, Cuiying; Fu, Wensheng; Yuan, Hua; Hu, Pingping; Liu, Yang
Abstract : Guidelines of how to select nitrogen-doping reagents for enhancing photoluminescence of carbon nanodots are proposed by taking hexamethylenetetramine as a typical example. Abstract : Doping with nitrogen in the synthesis of carbon nanodots has been demonstrated to be an effective approach to manipulate their composition/structure and thus largely enhance photoluminescence (PL). However, the guidelines for how to select an effective and universal nitrogen-doping reagent are not clear. In this work, nitrogen-doped carbon nanodots (N-CDs) with high PL quantum yield (62.8%) and good photostability are prepared in aqueous solution, employing hexamethylenetetramine (HMTA) as a nitrogen-doping reagent. It was found that the PL of CDs is always significantly enhanced by the introduction of HMTA, regardless of using organic acids or carbohydrates as carbon sources. Taking HMTA as a typical example, guidelines for the selection of a robust nitrogen-doping reagent for the hydrothermal synthesis of N-CDs are concluded. Moreover, the results of cellular cytotoxicity assessment and optical imaging demonstrate excellent biocompatibility as well as biolabeling and anti-counterfeiting potential of the N-CDs.